Bima Arya's Political Communication Strategy In Efforts For Personal Branding On Instagram Social Media - Susilowati, Susilowati; Kussanti, Devy Putri; Suryani, Ita; Armelsa, Dhefine; Atmaja, Jaka (Universitas Riau Kepulauan, 2025)
This study examines Bima Arya's political communication strategy in his efforts for personal branding on Instagram, using a pragmatism paradigm and a qualitative approach. In the rapidly growing digital era, social media has become an important platform for politicians to build and manage their public image. This research uses a qualitative method with a constructivism paradigm, as the aim of the study is to gain a deep understanding of how Bima Arya communicates his self-image through Instagram and how the audience responds to and constructs meaning from this communication. The findings show that content emphasizing direct engagement, transparency, and responsiveness to public issues has proven effective in increasing audience engagement and strengthening a politician's positive image. Bima Arya has successfully maintained his brand image as